2020
DOI: 10.3390/cells9051204
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor EB Reduces the Intraneuronal Accumulation of the Beta-Secretase-Derived APP Fragment C99 in Cellular and Mouse Alzheimer’s Disease Models

Abstract: : Brains that are affected by Alzheimer’s disease (AD) are characterized by the overload of extracellular amyloid β (Aβ) peptides, but recent data from cellular and animal models propose that Aβ deposition is preceded by intraneuronal accumulation of the direct precursor of Aβ, C99. These studies indicate that C99 accumulation firstly occurs within endosomal and lysosomal compartments and that it contributes to early-stage AD-related endosomal-lysosomal-autophagic defects. Our previous work also suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…TFEB activates the different steps of autophagy, from its initiation to the fusion of autophagosomes with lysosomes, but it also stimulates the biogenesis of lysosomal hydrolyses and regulates lysosomal acidification ( 191 ). Indeed, in animals, TFEB activation has been found to efficiently decrease C99 levels ( 192 , 193 , 194 ) and to ameliorate cognitive function, whereas it does not seem to produce any harmful effects in wild-type animals ( 143 ). The recent findings concerning TFEB activation by a curcumin analog are promising, because of the lack so far of specific TFEB-activating molecules.…”
Section: Alternative Strategies To Decrease C99 Buildupmentioning
confidence: 99%
“…TFEB activates the different steps of autophagy, from its initiation to the fusion of autophagosomes with lysosomes, but it also stimulates the biogenesis of lysosomal hydrolyses and regulates lysosomal acidification ( 191 ). Indeed, in animals, TFEB activation has been found to efficiently decrease C99 levels ( 192 , 193 , 194 ) and to ameliorate cognitive function, whereas it does not seem to produce any harmful effects in wild-type animals ( 143 ). The recent findings concerning TFEB activation by a curcumin analog are promising, because of the lack so far of specific TFEB-activating molecules.…”
Section: Alternative Strategies To Decrease C99 Buildupmentioning
confidence: 99%
“…The authors proposed a model in which TFEB plays an active role in the secretion of mutant tau via lysosomal exocytosis mediated by TFEB and Transient Receptor Potential Mucolipin 1 (TRPML1) signaling [ 125 ]. Accordingly, astrocyte-specific TFEB overexpression in the hippocampus of PS19 mice was able to reduce tau spreading from the ipsilateral to the contralateral hippocampus [ 126 ]. A recent study reported that TFEB overexpression in another AD mouse model is responsible for a reduction of the levels of the β-secretase-derived β-amyloid precursor protein fragment C99, which is a precursor of the toxic Aβ peptide.…”
Section: Tfeb and Autophagy In Neurodegenerationmentioning
confidence: 99%
“…This suggests that TFEB activation is an important strategy for preventing the accumulation of the early neurotoxic catabolite of AD. 143 A disintegrin and metalloproteinase 10 (ADAM10)…”
Section: Therapeutic Effects Of Tfeb Overexpression In Neurodegenerat...mentioning
confidence: 99%
“…The beneficial effects mediated by TFEB have been demonstrated in multiple mouse and cell models of AD addressing Aβ and tau pathology. 33 , 142 , 143 With respect to Aβ, TFEB overexpression rescues the autophagic flux, accelerates Aβ 1–42 degradation by regulating the autophagy‐lysosome pathway, and alleviates Aβ 1–42 ‐induced toxicity by reducing oxidative stress. 144 Similarly, intracranial stereotaxic injection of AAV‐TFEB in hippocampal neurons of APP/PS1 mice leads to a reduction of APP, Aβ production, and amyloid plaque load by accelerating flux of the endosome‐lysosome pathway.…”
Section: Tfeb As a Therapeutic Target For Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation